2004
DOI: 10.1002/glia.20042
|View full text |Cite
|
Sign up to set email alerts
|

CD44 overexpression by oligodendrocytes: A novel mouse model of inflammation‐independent demyelination and dysmyelination

Abstract: The CD44 transmembrane glycoprotein family has been implicated in cell-cell adhesion and cell signaling in response to components of the extracellular matrix but its role in the nervous system is not understood. CD44 proteins are elevated in Schwann cells and oligodendrocytes following nervous system insults, in inflammatory demyelinating lesions, and in tumors. Here, we tested the hypothesis that elevated CD44 expression influences Schwann cell and oligodendrocyte functions by generating transgenic mice that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Sgk1 was induced in 3NP mice compared with control mice (2.7-fold induction) and was also significantly downregulated in 3NP mice treated with CBG (−1.41-fold repression). Although, in general, these results confirm that the molecular mechanisms underling HD physiopathology are quite different in 3NP and R6/2 murine models (see below), previous studies have confirmed the relation of these two genes with HD and other neuroinflammatory disorders [31,32].…”
Section: Study Of Neuroprotective Effects Of Cbg In 3np-lesioned Micesupporting
confidence: 79%
“…Sgk1 was induced in 3NP mice compared with control mice (2.7-fold induction) and was also significantly downregulated in 3NP mice treated with CBG (−1.41-fold repression). Although, in general, these results confirm that the molecular mechanisms underling HD physiopathology are quite different in 3NP and R6/2 murine models (see below), previous studies have confirmed the relation of these two genes with HD and other neuroinflammatory disorders [31,32].…”
Section: Study Of Neuroprotective Effects Of Cbg In 3np-lesioned Micesupporting
confidence: 79%
“…MOG was combined with complete Freund's adjuvant containing heat-inactivated mycobacterium tuberculosis as previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture experiments have demonstrated that HA blocks OPC maturation (Marret et al, 1994;Back et al, 2005), and studies in an adult rodent model have shown that HMW HA accumulation in chronic lesions of demyelination inhibits OPC maturation (Back et al, 2005). Intriguingly, mice engineered to overexpress CD44 also exhibit inflammation-independent demyelination (Tuohy et al, 2004). Moreover, our previous study showed that suppression of inflammation by COX2 inhibition or TNF␣ downregulation promotes myelination in this animal model (Vinukonda et al, 2010).…”
mentioning
confidence: 84%
“…TLR2/4 receptors are activated in cerebral ischemia, trauma, hemorrhage, and infection (Konat et al, 2006;Fischer and Ehlers, 2008;Rivest, 2009), and inhibition of TLR2/4 offers neuroprotection in several adult rodent models of brain injury (Lehnardt et al, 2007;Tang et al, 2007). CD44 levels are chronically elevated in demyelinating lesions of multiple sclerosis, and antagonizing CD44 promotes remyelination and neurological recovery (Tuohy et al, 2004;Guan et al, 2011). Hence, specific fragments of HA can induce white matter injury, which can potentially be reversed by degrading HA or by blocking its binding receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation